Strategi Pemasaran Produk Sepeda Motor Honda Menggunakan Fuzzy Teori Permainan - Adabawiyah, Robiatul (Universitas Islam Madura, 2022)
Honda motorcycles are a means of transportation that are inexpensive and more flexible than other means of transportation. Honda motorcycles themselves are the choice of consumers, because of their fuel economy, smooth engine sound, and good quality spare parts. Intense market competition has become a necessity in the business world (business). Companies must think of optimal marketing strategies and concepts based on consumer ratings of Honda motorcycles. The uncertainty of consumer assessment of the products used is interpreted using fuzzy. Determination of marketing strategy is done by using game theory. So that the most optimal strategy in the game is won by the exhibition promotion strategy.